Intangible cultural heritage as a resource for consolidating modern Ukrainian society - Chmil, Hanna; Kuznietsova, Inna; Mishchenko, Maryna; Oliynyk, Oleksandra; Demeshchenko, Violeta (Linguistics and Culture Review, 2021)
The relevance of this study lied in actualising the issue of increasing the level of social consolidation of Ukrainian society under the conditions of a number of political, economic, social, and cultural transformations. Intangible cultural heritage serves as the main resource for the establishment and development of national consciousness, which, in turn, strengthens integration processes within society. The purpose of the study is to prove the value of intangible cultural heritage in the modern life of Ukrainians and substantiate the need to preserve cultural values in the course of historical development as a powerful ethno-unifying factor. In the course of the study, general scientific methods, namely analysis, synthesis, induction, deduction, systematic, and comparative were used for logical and consistent presentation of the material. A critical approach to information allowed comprehensively and thoroughly examining the issue of cultural heritage as a unifying factor. As a result of the study, it was discovered that due to complex socio-political and globalisation processes, there is still a need to preserve the traditional heritage, which is an indicator of cultural independence, proving the uniqueness and originality of each nation. Therefore, in the course of the technologisation of society.